1963
DOI: 10.1021/j100805a013
|View full text |Cite
|
Sign up to set email alerts
|

Pressure—temperature—resistance Properties of Lanthanum, Bismuth, Neptunium, Plutonium, and Americium to 450° and 30 Kb.

Abstract: ponent 1 do not appear to be satisfactorily described component 1 is less than M,, to obtain sufficiently by the molecular theory in its present form. It may direct and precise information for a complete analysis. be necessary to measure them by diff ereiit experi-Acknowledgment.-This work was supported in mental means, especially when the molecular weight of part by a grant from the National ScTence Foundation.The actinide elements neptunium,.plutonium, and americium are materials of considerable interest to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1964
1964
1974
1974

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The RT La(I-II) transition was first observed by Bridgman [72,73] during V(p) studies, although similar studies by Vaidya and Kennedy [385] did not reveal the transition. It has since been confirmed by R(p) [75,231,277] and superconductivity [266,337,427] measurements, and X-ray studies [279,313] have shown that La(JI) has a fcc structure. A unique feature of this transition is that it apparently consists of two separable events that-occur at roughly the same pressure.…”
Section: Lanthanummentioning
confidence: 94%
See 2 more Smart Citations
“…The RT La(I-II) transition was first observed by Bridgman [72,73] during V(p) studies, although similar studies by Vaidya and Kennedy [385] did not reveal the transition. It has since been confirmed by R(p) [75,231,277] and superconductivity [266,337,427] measurements, and X-ray studies [279,313] have shown that La(JI) has a fcc structure. A unique feature of this transition is that it apparently consists of two separable events that-occur at roughly the same pressure.…”
Section: Lanthanummentioning
confidence: 94%
“…The data are shown in figure 58. McWhan [277] did some R(p) work on this element but found no reproducible features in the data at RT to about 36 khar.…”
Section: Americiummentioning
confidence: 94%
See 1 more Smart Citation
“…There are systems which, do not exhibit a discontinuity in the resistance accompanying a phase chane;e. Lanthanum is such a case. 5 .. A.…”
mentioning
confidence: 99%